Functionalization of hybrid poly(n‐isopropylacrylamide) hydrogels for Escherichia coli cell capture via adsorbed intermediate dye molecule. Issue 10 (11th November 2014) - Gregory, Jarod; Cannell, Jonathon; Kofron, Matthew; Yeghiazarian, Lilit; Nistor, Vasile
ABSTRACT Poly(n‐isopropylacrylamide) Laponite (PNIPAM‐Lap) hybrid hydrogels, which use the synthetic clay Laponite as a crosslinker, permanently adsorb cationic laser dyes out of solution. This proof‐of‐concept expounds on this capability by adsorbing an intermediate dye molecule and using it as the foundation for successfully conjugating microbial antibodies to the surface of a PNIPAM hydrogel. The study involves using acriflavinium chloride molecules, adsorbed by a PNIPAM‐Lap hydrogel from an acriflavine laser dye solution, as an intermediate molecule to attach antibodies raised against E. coli to the hydrogel and demonstrate cell capture. Furthermore, this system exemplifies a novel biotechnological platform for greatly expanding PNIPAM hydrogels' capabilities and applicability through conjugation chemistry to surface‐bound molecules. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41557.